Disclosure Policy and Industry Fluctuations - Bertomeu, Jeremy; Liang, Pierre Jinghong (Management Science, 2015)
This paper examines voluntary disclosures in a repeated oligopoly and their association with price-setting behavior and industry profits along industrial fluctuations. The analysis focuses on the collectively optimal equilibrium among oligopoly firms. We show that, in industries that are highly concentrated or feature low cost of capital, nondisclosure is prevalent and results in stable product prices and high profit margins. Otherwise, firms may selectively disclose to soften competition in the product market. Under partial disclosure, firms withhold information during sharp industry expansions or declines. Consequently, the disclosure policy dampens the dissemination of shocks to the industry. This paper was accepted by Mary Barth, accounting.